Um olhar semiótico sobre os materiais estruturados de ensino do estado de Mato Grosso - Sílvia Figueiredo de Sousa (2024)
Based on the observation of teaching and learning processes in the Brazilian public education during the period of the covid-19 pandemic and its repercussions on society, including a statement from the Ministry of Education and partner institutions about the lag of almost two years or more in students learning, we search for the structured teaching materials from the state of Mato Grosso, offered by the government to learning recomposing. Our objective is to investigate what discursive strategies were used in the structured materials to approach the public and awaken their interest in the content to be taught and learned. For that, we search in the statements of the structured material for occurrences of the enunciative and enunciative debridement mechanism to understand how the enunciator (author) discursively approaches the enunciatee teacher and student. We analyze excerpts froma discursive perspective at the structured Portuguese language material, from 2022, for 7th and 9th year classes. We examined the material at the discursive level by discursive semiotics, with the objective of observing the structures of the enunciation, on the categories of person, time and space and thematization and figurativization present in the materials. The base theoric is Barros (2005), Fiorin (2009, 2012), Tocaia (2014), and others works with the same research object. As results of the study, we identified a recurrence of enunciative debreasing to create effects of proximity between narrator and narratee, although enunciative strategies that create an effect of formality, objectivity and topicality in the material. Although some figures embody the theme of the covid-19 pandemic in parts of the material, we realize that the structured material does’nt support this theme and can be used even outside the context of post-pandemic learning recomposing. We observe excerpts with regionalization, but a global approach predominates on the standard norm of the Portuguese language and approaches to texts and genres for subjects who can be from any location.